Application of General Nursing Intervention Drawing Activities Towards Schizophrenia Patient with Hallucination - Antriska, Veva Mutiarasari (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
Schizophrenia is a mental disorder that is common throughout the world. People with schizophrenia can have difficulty orienting themselves to real life. Schizophrenia is a category of serious mental disorders that impact an individual's ability to feel, think and even behave, characterized by hallucinations, delusions and disturbances in thoughts, perceptions and behavior. Hallucinations are wrong perceptions about objects or events involving the five senses such as sight, sound, smell, touch and taste. Hallucinations have an impact that can make a person lose self-control, feel afraid, suspicious, feel insecure, anxious, confused, self-destructive, lack of attention, unable to make decisions. The aim of this research is to provide an overview of the application of generalist nursing interventions to patients with hallucinations through the application of distraction drawing activities to Mrs. N with hallucinatory nursing problems. The intervention was carried out on September 25-October 5 2023. The level of hallucination intensity was measured using the Psyrats instrument. The results showed that there was a decrease in the intensity level of hallucinations experienced from 31 to 1. This research proves that the application of generalist intervention with a distraction approach to drawing activities for the patient Mrs. N with hallucinatory nursing problems has been proven to reduce the intensity of hallucinations and signs of hallucinatory symptoms, as well as increasing the ability to control hallucinations.